2017
DOI: 10.1097/mib.0000000000001038
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy and Resilience Are Useful Predictors of Transition Readiness Scores in Adolescents with Inflammatory Bowel Diseases

Abstract: This is the first study to identify a reliable predictor of transition readiness scores in adolescents with IBD that does not seem to be influenced by age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
71
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 20 publications
2
71
0
2
Order By: Relevance
“…[1][2][3]. It is the ability to overcome these challenges, including following complex medical recommendations and successfully managing their chronic illness, which leads to successful disease management and ultimately successful transition from pediatric to adult care [1,2,[4][5][6][7][8][9][10][11][12][13][14]. Improving self-management and health behaviors while preparing adolescents for a successful transition from pediatric to adult care remains a critical area of need to minimize the short-term and long-term consequences of poor self-management behaviors on health outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3]. It is the ability to overcome these challenges, including following complex medical recommendations and successfully managing their chronic illness, which leads to successful disease management and ultimately successful transition from pediatric to adult care [1,2,[4][5][6][7][8][9][10][11][12][13][14]. Improving self-management and health behaviors while preparing adolescents for a successful transition from pediatric to adult care remains a critical area of need to minimize the short-term and long-term consequences of poor self-management behaviors on health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Resilience or the ability to bounce back when faced with adversities has been shown to correlate with transition readiness and disease outcomes [9,[15][16][17]. The concept of resilience emerged in the mid-1970s when psychologists recognized that certain individuals were better able to overcome stressors such as life conflicts, health problems, and trauma compared to other peers [17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During transition from juvenile to adult-centred care, both self-efficacy (SE) and resiliency were found to independently and significantly predict better transition [97]. In response, Carlsen et al developed an e-health transfer concept to assess patient-reported outcomes, including selfefficacy, resilience, stress response among adolescents with IBD transitioning to healthcare [98].…”
Section: Resilience In Inflammatory Bowel Diseasementioning
confidence: 99%
“…However we still do not yet fully understand who is and who is not vulnerable, and as yet, there is limited evidence that resilience training works in this population. Resilience may be associated with a readiness for transition to adult care in younger IBD populations, but further work is needed to establish its role in older patients. Furthermore, it may be challenging to intervene in this way at disease onset given that patients may be unwell at this time.…”
mentioning
confidence: 99%